Pemanfaatan Kertas Bekas, Serabut Kelapa (Socos nucifera) dan Kulit Singkong (Manihot utilissima) Untuk Pembuatan Kertas Daur Ulang - Zurorotul Munashifah; Heru Subaris Kasjono; Bambang Suwerda (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2018)
Kalipoh Village, Ayah Discrit Kebumen, Regency is a waste-producing area such as waste paper, coconut fibre and cassava peels that have not been well managed. The impact of this waste can cause environmental health problems. These three types of waste have cellulose content that can be utilized to make recycled paper. This study aims to determine water absorption, tensile strength, and community acceptance with pre-experimental research design posttest only design analyzed descriptively. The results showed that the best water absorption strength and paper tensile strength were a variation of 1: 1: 2 with a yield of 76 mm and 2,683 N / mm. Whereas based on the result of physical test and public acceptance that recycle paper of variation I have a slightly coarse texture, the fibre is slightly visible and the pale; variation II has a coarse texture, visible fibre and pale colour, while variation III has a rather coarse texture, rather visible fibre and vibrant colour. The community also deeply appreciates the innovation of recycled paper making.